Evaluate.
-|-7 + 3|
A.-4
B.4
C.-10

-|-7 + 3|; -7 + 3 = -4

Question

Asked 6/20/2011 8:29:00 AM

Updated 4/26/2014 6:54:44 PM

1 Answer/Comment

Rating

3

-|-7 + 3|;

-7 + 3 = -4

-7 + 3 = -4

Added 4/26/2014 6:54:44 PM

This answer has been confirmed as correct and helpful.

Solve |2x - 5| = 4.

Question

Not Answered

Updated 8/24/2014 3:46:36 PM

1 Answer/Comment

|2x - 5| = 4

2x - 5 = -4 or 2x - 5 = 4

2x - 5 = -4;

2x = -4 + 5;

2x = 1;

x = 1/2;

2x - 5 = 4;

2x = 4 + 5;

2x = 9;

x = 9/2;

x = 1/2 or x = 9/2

2x - 5 = -4 or 2x - 5 = 4

2x - 5 = -4;

2x = -4 + 5;

2x = 1;

x = 1/2;

2x - 5 = 4;

2x = 4 + 5;

2x = 9;

x = 9/2;

x = 1/2 or x = 9/2

Added 8/24/2014 2:47:21 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/24/2014 3:46:37 PM]

Solve the following system of equations by the substitution method.
"5x = y + 6,"
"2x - 3y = 4"

Question

Not Answered

Updated 9/14/2014 1:09:10 AM

6 Answers/Comments

janezshun, please make sure to clearly type your solutions by using proper spacing.

Added 9/10/2014 7:00:16 AM

Hi andrew , for these question, Can I simplify or didn't use to add the calculation steps? I think I can't simplify it ,because the question asked to use the substitution method.

Added 9/10/2014 8:01:36 AM

The solution for 5x = y + 6, 2x - 3y = 4 is x = 14/13, y = -8/13.

From 5x = y + 6 , we can get y = 5x - 6, which we can put it into the 2th equation.

2x - 3y = 4

2x - 3 (5x - 6) =4

-13x + 18 =4

x = 14/13

put x = 14/13 into the y = 5x - 6 , we can get the value of y

y= 5x - 6

y= 5*14/13 - 78/13

y= 70/13-78/13

y= - 8/13

From 5x = y + 6 , we can get y = 5x - 6, which we can put it into the 2th equation.

2x - 3y = 4

2x - 3 (5x - 6) =4

-13x + 18 =4

x = 14/13

put x = 14/13 into the y = 5x - 6 , we can get the value of y

y= 5x - 6

y= 5*14/13 - 78/13

y= 70/13-78/13

y= - 8/13

Added 9/14/2014 1:09:10 AM

Evaluate. -|-7 + 3|
**Weegy:** Two Negatives would equal a positive so the equation would be 7+ -3= Which would equal a positive 4 (More)

Question

Expert Answered

Updated 1/12/2015 8:55:41 AM

1 Answer/Comment

Simplify (5ab^4 c)(-abc^2).

Question

Expert Answered

Updated 6/6/2015 12:20:43 PM

1 Answer/Comment

(5ab^4 c)(-abc^2)

= -5a^2b^5c^3

= -5a^2b^5c^3

Added 5/3/2015 3:08:35 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/6/2015 12:20:39 PM]

Evaluate the following expression.
(8^1)^0

Question

Not Answered

Updated 6/20/2011 12:32:45 PM

1 Answer/Comment

27,210,821

questions answered

There are no comments.